Importance, Popularity and Elements of Educational Platforms – A Study of the Opinions of Students from Poland, Ukraine and Kazakhstan - Przybyła-Kasperek, Małgorzata; Chromiński, Kornel; Smyrnova-Trybulska, Eugenia; Morze, Nataliia; Bazarbayeva, Ainur (International Journal of Research in E-learning, 2023)
This article presents a comparative international research study analyzing the opinions of students from Poland, Ukraine, and Kazakhstan regarding the importance, popularity, and elements of educational platforms in the field of computer science. The study employed the Kruskal-Wallis test for statistical analysis. The research questions addressed are as follows: RQ1: What are educational platforms in general, and which specific platforms are most popular among students from Poland, Ukraine, and Kazakhstan? RQ2: Which topics are most frequently searched for on educational platforms, and what motivates students from these countries to engage in learning through educational platforms? RQ3: How do students from Poland, Ukraine, and Kazakhstan evaluate the usefulness of different types of content posted on educational platforms, and do they use various platforms to share their code? Two hypotheses are proposed: firstly, that the country of origin of the student does not significantly affect the frequency of use of educational platforms, and secondly, that the country of origin does influence the choice of courses students are interested in on educational platforms. The most popular topics on these platforms are programming and computer networks, with students from Kazakhstan also displaying a keen interest in subjects related to artificial intelligence and computer graphics. Additionally, this study analyzes the conditions of learning and teaching in specialized modules at each university, including teacher requirements, curriculums, and the potential for practical implementation of new knowledge by students. Furthermore, the study examines course elements that are most essential to students, such as video recordings of lectures, tutorials/instructional videos, practical tasks, and solutions to tasks. The article concludes with a discussion and summary of the findings.